Analysis of the Influence of WOM, Physical Environment and School Image on the Decision to Choose a School with Intention to Choose a School as a Mediating Variable (Study on Students of SMKN 47 Jakarta) - Miftahul Huda; Adi Nurmahdi (Indonesian Journal of Business Analytics, 2025)
This study aims to determine and analyze the influence of word of mouth, physical environment and school image on the decision to choose a school with the intensity of choosing a school as a mediating variable (a study on students of SMKN 47 Jakarta). The population used in this study were students enrolled at SMKN 47 Jakarta in the 2024/2025 academic year. The method used in this study was probability sampling with a simple random sampling technique, with the criteria being students of SMKN 47 Jakarta enrolled in the 2024-2025 academic year, with a sample size of 187 respondents. The data analysis method used Structural Equation Model-Partial Least Square (SEM-PLS). The results of this study indicate that word of mouth and the physical environment have a positive and significant influence on the intensity of choosing, while the image of the school does not have a significant influence on the intensity of choosing. Word of mouth, the physical environment and the image of the school and the intensity of choosing have a positive and significant influence on the decision to choose a school. The intention to choose is a partial mediation between word of mouth and the physical environment on the decision to choose a school, while there is no mediation on the image of the school.